Keharmonisan Keluarga Tenaga Kerja Wanita Perspektif Psikologi Keluarga Islam - Umi Rohmawati; Ika Rusdiana (Fakultas Syariah Institut Agama Islam Negeri Ponorogo, 2021)
Nowadays, due to the complex family economic problems, it is the reason for a wife to become a TKW abroad to improve the family's economy. This study aimed to determine the psychological analysis of Islamic families on the communication patterns of TKW families and to find out the psychological analysis of Islamic families on conflict resolution in TKW families from Gajah Village Ponorogo. The method used a qualitative method with data collection techniques with interviews and documentation. The results showed that the communication pattern of the TKW families in Gajah Village was by the Qur'an about communication ethics, namely: trustworthy, not lying, and fair. Conflict resolution in realizing a harmonious family in the TKW family in Gajah Village uses four conflict resolutions contained in QS an-Nisa' verse 35, namely: al-Ma'ruf (tenderness and harmony between husband and wife), al-Ma'ruf (tenderness and harmony between husband and wife), al-Sabru (patience), Tahammul al-Ada (freedom in conveying and receiving partner's opinion) and al-Wa'zu (advice).